«Хазарская Сугдея» – историческая реальность или историографический миф? - Могаричев, Ю.М.; Сазанов, А.В. (Хазарский альманах, 2020)
The authors revises controversial issue on Sougdea status in “Khazar Period”. In authors` view, full range of sources show that Sougdea in 8th–9th century AD was Byzantine city and there is no indication of the Khazarian government.